Numerical investigation on heat transfer enhancement of falling film evaporation by surface structure optimization - Wei Zhang; Ben Niu; Zhen Liu; Zhaoliang Wang (Desalination and Water Treatment)
This study employs the VOF model to conduct a numerical simulation of two-dimensional external falling film evaporation on micro-ribbed tubes. It aims to investigate the impact of various structural parameters of micro-ribs on the flow and heat transfer performance of the external falling film and determine the optimal tube configuration under different conditions. The results show that the maximum deviation between the numerical calculation results and Parken's experimental results is less than 8 %. The results show that triangular micro-ribbed tubes exhibit a higher average heat transfer coefficient (hav) at moderate to high Γ (spray density). For the triangular-rib tubes, the hav shows a trend of initially increasing and then decreasing concerning structural parameters H(rib height), W(rib width), and N(rib number). At H= 0.4 mm, W= 1.6 mm, N = 32, compared with the smooth tube, the hav of the micro-ribbed tube is increased by 34.5 %. The alteration of structural parameters affects the local heat transfer coefficients (h) of the micro-ribbed wall (upper wall and lower wall) and the base-tube wall. The center of the upper wall and the base-tube wall of the micro-ribbed tube is the high heat transfer area, while the front and end of the lower wall and base wall are the low heat transfer area. The increased disturbances caused by vortices forming in the inter-rib region are primarily responsible for enhancing the hav. The size of the inter-rib region is the main reason for the generation of vortices. In addition, the thickness of the liquid film outside the micro-ribbed tube and the temperature gradient inside the liquid film also have important effects on heat transfer.